Navigating Turbulence: The Swiss Franc’s Resilience as a Safe-Haven Currency - Raikisto, Valtteri (My University, 2025)
The Swiss franc (CHF) has long been regarded as a stable currency, often strengthening during periods of global and financial uncertainty. This study examines the key factors influencing the Swiss franc’s valuation, focusing on its response to different macroeconomic shocks. The motivation behind this work lies in the recurring appreciation of the franc, particularly during global crises. This study investigates whether the franc’s movements align with traditional exchange rate theories and whether its role as a “safe haven” is supported by existing empirical evidence. To analyze the franc’s reaction to various economic shocks, a Vector Autoregressive (VAR) model is employed. This model allows for the examination of dynamic interactions between the exchange rate and classic macroeconomic variables, such as interest rates, inflation, and foreign direct investment. Additionally, it incorporates less commonly analyzed factors, such as oil prices and the Geopolitical Risk Index (GPR). The Impulse Response Function (IRF) is applied to assess how the franc responds to shocks in these variables over time. The findings reveal that the franc appreciates in response to inflationary pressures in the United States, while a slight appreciation is also observed in reaction to geopolitical risks. Additionally, the response to oil price shocks is slightly positive, challenging the classical assumption regarding small open economies. There is practically no impact of foreign direct investment (FDI) innovations on the exchange rates, which aligns well with previous studies. These results indicate that Swiss authorities should maintain stable interest rates, as they contribute to long-term price stability. Given that the franc tends to appreciate over time—especially during crises—excessive currency strength could harm Swiss exports and economic competitiveness. This research contributes to the broader understanding of exchange rate dynamics by providing empirical insights into the Swiss franc’s behavior. The study underscores the importance of considering external economic shocks when assessing exchange rate stability and highlights the need for proactive monetary policy responses to ensure long-term economic stability.

Sveitsin frangia (CHF) on pitkään pidetty vakaana valuuttana, joka vahvistuu usein globaaleissa ja taloudellisissa epävarmuustilanteissa. Tämä tutkimus tarkastelee tärkeimpiä tekijöitä, jotka vaikuttavat Sveitsin frangin arvonmuodostukseen. Tutkimus keskittyy pääosin frangin reaktioihin erilaisiin makrotaloudellisiin shokkeihin. Työn taustalla on frangin toistuva arvon nousu erityisesti maailmanlaajuisten kriisien aikana. Tutkimus pyrkii selvittämään, vastaavatko frangin liikkeet perinteisiä valuuttakurssiteorioita ja tukeeko empiirinen aineisto sen asemaa ”turvasatamana”. Analysoidakseen frangin reaktiota taloudellisiin shokkeihin käytetään vektoriautoregressiivistä (VAR) mallia. Tämä malli mahdollistaa dynaamisten vuorovaikutusten tarkastelun valuuttakurssin ja perinteisten makrotaloudellisten muuttujien, kuten korkojen, inflaation ja ulkomaisten investointien, välillä. Lisäksi malli sisältää harvemmin analysoituja tekijöitä, kuten öljyn hinnan ja geopoliittisen riskin indeksin (GPR). Impulse Response -funktion(IRF) avulla arvioidaan, miten frangi reagoi näiden muuttujien shokkeihin ajan myötä. Tulokset osoittavat, että frangi vahvistuu vastauksena Yhdysvaltain inflaatiopaineisiin, ja lievää arvonnousua havaitaan myös geopoliittisten riskien yhteydessä. Lisäksi frangin reaktio öljyn hinnan muutoksiin on lievästi positiivinen, mikä haastaa perinteisen käsityksen pienten avoimien talouksien käyttäytymisestä. Suoria ulkomaisia investointeja (FDI) koskevilla muutoksilla ei käytännössä ole vaikutusta valuuttakurssiin, mikä tuke aiempia tutkimuksia. Tulosten perusteella Sveitsin viranomaisten tulisi ylläpitää vakaata korkotasoa, sillä se edistää pitkän aikavälin hintavakautta. Koska frangi on taipuvainen vahvistumaan ajan myötä – erityisesti kriisiaikoina – sen liiallinen arvonnousu voi haitata Sveitsin vientiä ja taloudellista kilpailukykyä. Tämä tutkimus laajentaa ymmärrystä valuuttakurssidynamiikasta tarjoamalla empiirisiä näkemyksiä Sveitsin frangin käyttäytymisestä. Se korostaa ulkoisten taloudellisten shokkien huomioon ottamisen tärkeyttä valuuttakurssivakauden arvioinnissa ja tuo esiin ennakoivan rahapolitiikan tarpeen taloudellisen vakauden varmistamiseksi pitkällä aikavälillä.
Keywords: fi=Taloustiede|en=Economics|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|